Effect of the Supportive – Educative Program on Infection Prevention Practices among Caregivers of Pediatric Cancer Patients - Sarinosak, Narisara; Klunklin, Pimpaporn; Meechamnan, chutima (Princess of Naradhiwas University Journal, 2025)
The purpose of this quasi-experimental research was to investigate the effects of a supportive - educative program on infection prevention practices among caregivers of children with cancer. The participants were caregivers of pediatric cancer patients receiving chemotherapy at Maharaj Nakorn Chiang Mai Hospital. The sample of 48 caregivers were divided into two groups: the experimental group and the control group, with 24 per group. The control group received conventional nursing care, and the experimental group received the supportive – educative program on infection prevention practices. The assessment tools used in the research consisted of the supportive - educative program on infection prevention practices in caregivers of pediatric cancer patients; a demographic information questionnaire of pediatric cancer patients and caregivers; and an infection prevention practice questionnaire in caregivers of children with cancer. Content validity was checked by experts, resulting in a content validity index of 0.98. The reliabilities testing value was 0.94. Data were analyzed using descriptive statistics, Wilcoxon signed-rank test, Mann-Whitney U test, and analysis of covariance. The results showed that the score for infection prevention practices of caregivers of children with cancer in the experimental group was statistically significantly higher than that of the control group. The score for the infection prevention practice of caregivers of children with cancer in the experimental group was statistically significantly higher after receiving the supportive educative program on infection prevention practice than before receiving the program (p < .05). These findings suggest that nurses can implement the supportive–educative program to enhance infection prevention practices among caregivers of children with cancer.